2021
DOI: 10.54820/gtfn9743
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation: Challenges for Human Resources Management

Abstract: The global economic situation and need to be better prepared for competitive challenges put pressure on modern companies to shift toward automation and digitalization. As a consequence of rapid technological development and the speed of change and therefore forced transformation of business models and work design, organizations are faced with a need for a massive change of features and an extended role of HR management processes. To be able to drive future organizational performance, HR leaders and professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Furthermore, alongside these changes, digital transformation also opens doors to new opportunities in HR development through various online learning platforms and available digital resources [18]. With easier and more flexible access to online courses, webinars, and various other resources, employees now have the opportunity to continuously develop their skills according to evolving business needs [19].…”
Section: Figure 1 Flowchart Methodologymentioning
confidence: 99%
“…Furthermore, alongside these changes, digital transformation also opens doors to new opportunities in HR development through various online learning platforms and available digital resources [18]. With easier and more flexible access to online courses, webinars, and various other resources, employees now have the opportunity to continuously develop their skills according to evolving business needs [19].…”
Section: Figure 1 Flowchart Methodologymentioning
confidence: 99%
“…Increasing employee digital competence has become the main focus in facing digital transformation challenges. The literature review highlights that with digital transformation, employees need to have skills and a deep understanding of technology to remain relevant and effective in an increasingly digitalized work environment (Barišić, 2021) (Hang, 2021). This includes not only knowledge of the latest software and applications, but also an understanding of how those technologies can be applied effectively in the context of their work.…”
Section: Increasing Employee Digital Competencementioning
confidence: 99%
“…The practical results showed that there is the significant and positive correlation between digital transformation and HRM practices. Moreover, the findings asserted on the significant and positive effect of all dimensions of digital transformation on all dimensions of Human resources management (Recruitment and selection, training and development, and performance appraisal, compensation, performance management) Barišić, Barišić & Miloloža (2021) were interested in analyzing the impact of digital transformation which measured by (Strategy, organizational culture, Transformational leadership, and human resources) on human resources management practices (Recruitment and selection, training and development, and performance appraisal and compensation). Depending on Qualitative analysis, the findings showed that digital transformation acts as critical motivator for developing HRM practices as the application of digital technologies, the ways of hiring and selecting employees have changed.…”
Section: Studies Show Relationship Between Digital Transformation And...mentioning
confidence: 99%